Born out of Sorrow Essays on Pietermaritzburg and the KwaZulu-Natal Midlands under Apartheid, 1948-1994 - Merrett, Christopher; Merrett, Christopher (Natal Society Foundation, 2021)
HALF the size of New York cemetery and twice as dead: this much-quoted, wry comment is generally attributed to the satirical writer Tom Sharpe who worked in Pietermarizburg in the 1950s. Also described as 'sleepy hollow' and the 'last outpost of the British Empire', Pietermaritzburg in fact possesses a rich history that highlights many key areas of South Africa's past. This is particularly true of the apartheid period. This is the first book published on the history of the city and region as a whole in over thirty years. It contains chapters on urban geography, the regional civil war, detention without trial, the black trade union movement, and political trials; biographical contributions on Chief Mhlabunzima Maphumulo and women of the Black Sash; and organisational memoirs of the Pietermaritzburg Agency for Christian Socal Awareness, Kupugani and the Association for Rural Advancement. The object of this series is to present fresh perspectives on the city and region's apartheid history. It takes a position that South Africa was liberated by all of its people - not one particular self-regarding vanguard movement with its hegemonic, one-dimensional views.